COGNITIVE-BEHAVIORAL APPROACH AND THE ROLE OF PHYSICAL ACTIVITY IN THE TREATMENT OF MUSCULOSKELETAL PAIN IN ATHLETES - Ortenburger, Dorota Elżbieta; Wąsik, Jacek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The importance of a cognitive-behavioral approach is richly documented in world scientific literature. In the light of the current knowledge about the determinants of pain treatment, the significance of psychological factors for the course and effects of analgesic therapy becomes more comprehensible. Many psychological processes have an influence on both the experience of pain and the treatment outcome. The factors like cognitive interpretation of pain, level of activity and emotional states of musculoskeletal pain sufferers are very important.The research referred to in this work makes a part of a long-term research programme the subsequent stages of which are analysed based on the literature of the subject that can assist in interpreting the new findings within dependencies between psychological factors and functioning in the case of the persons who cope with pain. Integration of psychological findings about attitude to pain into physical therapy treatment would seem to have potential to enhance outcomes. In this work we are presenting the problem in a context i.e. in the context of a role of cognitive-behavioral approach approach. The purpose of the article is to present the role of cognitive-behavioral approach in the field of applications that aim at supporting people who are involved in sport activity and cope with musculoskeletal pain-related ailments.